PROCESS AND SYSTEMS When patients (and families) raise the alarm: Patient and family activated rapid response as a safety strategy for hospitals. Issue 3 (2021) - Bucknall, Tracey; Quinney, Rett; Booth, Lisa; McKinney, Aidín; Subbe, Christian P; Odell, Mandy
No abstract available